(untitled) (Scientific journal of the Fergana State University, 2026)
In the 5th century AD, the Huns originating from present-day Central Asia, led by Attila, advanced into Europe. They captured Constantinople and compelled the Byzantine emperors to pay substantial tribute. Subsequently, Attila confronted the Western Roman Empire’s forces in Gaul (modern-day France), and soon after, the Huns entered Italy. Following a meeting with the Pope, Attila halted his campaign toward Rome. On their return from Italy, the Hunnic army settled in Central Europe, establishing permanent residence. The Latin term “Hungaria” (known as “Hungary” in English) is derived from the name of the Huns and forms the basis of the modern Hungarian state’s name. For centuries, Hungary’s scholarly and political circles have preserved the memory of their Turkic roots and sought to maintain ties with Turkic peoples. However, geographic distance has complicated these connections. Additionally, due to the Huns’ historical threat to Rome and their Eastern origins, their descendants were often met with estrangement in Europe.